DNA binding triggers tetramerization of the glucocorticoid receptor in live cells - Presman, Diego Martin (2016)
Transcription factors dynamically bind to chromatin and are essential for the regulation of genes. Although a large percentage of these proteins appear to self-associate to form dimers or higher order oli gomers, t he stoichiometry of DNA-bound transcription factors has been poorly characterized in vivo. The glucocorticoid receptor (GR) is a ligandregulated transcription factor widely believed to act as a dimer or a monomer. Using a unique set of imaging techniques coupled with a cell line containing an array of DNA binding elements, we show that GR is predominantly a tetramer when bound to its target DNA. We find that DNA binding triggers an interdomain allosteric regulation within the GR, leading to tetramerization. We therefore propose that dynamic changes in GR stoichiometry represent a previously unidentified level of regulation in steroid receptor activation. Quaternary structure analysis of other members of the steroid receptor family (estrogen, androgen, and progesterone receptors) reveals variation in oligomerization states among this family of transcription factors. Because GR's oligomerization state has been implicated in therapy outcome, our findings open new doors to the rational design of novel GR ligands and redefine the quaternary structure of steroid receptors.